2015
DOI: 10.1109/tthz.2015.2476962
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Computation of Temperature Elevation in Human Skin Due to Electromagnetic Exposure in the THz Frequency Range

Abstract: The ongoing development of new applications in the terahertz (THz) frequency range, such as wireless communication systems, full-body scanners, or other imaging procedures for biological and medical techniques, rapidly increases the number of persons who are potentially exposed to the electromagnetic radiation of those devices. Studies of thermal effects in humans caused by electromagnetic (EM) exposure with frequencies in the THz frequency range can rarely be found in the literature. In this paper, a method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To better determine the thermal and nonthermal effects of THz radiation, several key elements, such as reliable THz [ 2 3 _ T D $ D I F F ] equipments and dosimetric tools, as well as standardized designs and analyses, must be carefully considered in future experimental studies [85]. As a complementary method, the recently developed theoretical modeling used in the thermal analysis of tissue damage thresholds and temperature developments should have a more important role in future studies [100,101]. Moreover, few studies concerning measures to protect researchers from THz radiation have been reported due to a lack of risk assessment data.…”
Section: Biological Effects: Increasing Concernsmentioning
confidence: 99%
“…To better determine the thermal and nonthermal effects of THz radiation, several key elements, such as reliable THz [ 2 3 _ T D $ D I F F ] equipments and dosimetric tools, as well as standardized designs and analyses, must be carefully considered in future experimental studies [85]. As a complementary method, the recently developed theoretical modeling used in the thermal analysis of tissue damage thresholds and temperature developments should have a more important role in future studies [100,101]. Moreover, few studies concerning measures to protect researchers from THz radiation have been reported due to a lack of risk assessment data.…”
Section: Biological Effects: Increasing Concernsmentioning
confidence: 99%
“…We consider the case of EMSs, where besides EM, the thermal domain is present in the form of heat developing [24] or results in undesirable heating [25][26][27][28].…”
Section: Em and Thermalmentioning
confidence: 99%
“… 34 , 41 , 165 , 166 Such mechanism is predominantly observed when using CW THz emitters. Mathematical modeling of THz-radiation interactions with different biological tissues 167 , 168 shows that even quite low duration of THz exposure (such as few milliseconds) can cause notable increase in the tissue temperature. 168 , 169 An increase in the cornea temperature of up to 70°C was shown when it was exposed to a CW 1.0 THz radiation with the irradiance of ; see Fig.…”
Section: Terahertz Exposure Of Biological Objects With Different Levels Of Organizationmentioning
confidence: 99%